Green Performance Management Practices in Enhancing Employee Green Behaviour at Mercure Bali Legian - I Nengah Sudiarta; Ni Gst Nym Suci Murni; Ni Made Ernawati (International Journal of Green Tourism Research and Applications, 2026)
This study examines the influence of Green Performance Management (GPM) on Employee Green Behaviour (EGB) and develops a model of GPM practices that enhance environmental performance at Mercure Bali Legian. A mixed-method approach was employed, combining quantitative and qualitative techniques. Quantitative data were obtained through a survey of 85 employees, selected using purposive sampling, and analysed with Pearson correlation and simple linear regression using SPSS version 26. The results revealed a significant positive relationship between GPM and EGB, with a correlation coefficient of r = 0.344 and a determination coefficient (R²) of 0.119, indicating that 11.9% of the variation in EGB can be attributed to GPM practices. Qualitative findings, supported by interview excerpts and FGD validation, revealed that green initiatives remain concentrated at the managerial level with limited individual accountability. Qualitative data were collected through interviews with department heads and staff, observations, and validated through a Focus Group Discussion (FGD) with the management team. Findings highlighted that while GPM practices such as environmental goal setting, green KPIs, waste management, and sustainable procurement were implemented, employee behavioural consistency remained limited due to weak accountability and inconsistent training. The study concludes that GPM exerts a positive yet relatively modest effect on EGB. To strengthen outcomes, it is recommended that the hotel improve integration of GPM practices through structured dissemination, routine training, individualized performance monitoring, and formal feedback mechanisms. These enhancements are expected to increase employee engagement in sustainability initiatives and align behaviour more effectively with environmental performance.